Development and Challenge Sharia Banks in the Middle East - Abdullah Ashira (International Journal of Science and Society, 2020)
The development of Sharia Economics now shows quite encouraging developments. Although there is still no form of sharia economy itself agreed by the scholars. The key to sharia economics is of course the Sharia Bank. The strength of the non-ribbon business that became the Backbond of Bank Syarih has been recognized as a solid source in dealing with various monetary problems either micro or macro. This paper will discuss about how the economic potential of the middle east, the role of Islamic banking in the economy in it. The rapidly expanding economy of the Middle East has also provoked international banks to participate in developing the banking industry in the Middle East. Several case studies on middle east countries show how the challenges facing the banking world. From the different views of the ulama on the banking system, to the ease of transaction services that are favored and desirable to the public, even to the insurance despite the demand and bundling with banking products, and it turns out 70% of the bank's customers eventually transact insurance. It is hoped that this article can give us an idea of how Sharia economy develops in this country of origin of Islam. Then how is the middle eastern economy developed with a solid and solid Islamic banking system.